High‐sensitivity troponin T in marathon runners, marathon runners with heart disease and collapsed marathon runners. (17th February 2019) - Leckie, Todd; Richardson, Alan; Watkins, Emily; Fitzpatrick, Daniel; Galloway, Rob; Grimaldi, Rachael; Roberts, Andrew; Baker, Polly
Abstract : Endurance exercise is an established cause of cardiac troponin (cTn) elevation, of further interest is whether this rise represents clinical significance. This study compared cTnT rise in three cohorts of marathon runners using a high‐sensitivity assay; control runners, those with known heart disease and runners who collapsed at the finish line. Control runners (n = 126) and runners with heart disease (n = 12) were prospectively recruited with cTnT levels measured pre‐race and at race completion. Collapsed runners (n = 15) were retrospectively recruited. A mixed model ANCOVA was used to compare the three groups. Pre‐race median cTnT for the control group and heart disease groups was 3.9 ng/L (IQR 3.1 ng/L) and 4.1 ng/L (IQR 3.4 ng/L). Post‐race values for the three groups were control 45.6 ng/L (IQR 42.5 ng/L), heart disease 41.2 ng/L (IQR 36.1 ng/L), and collapsed 41.9 ng/L (IQR 57.8 ng/L). Post‐race cTnT and cTnT change were significantly correlated with pre‐race cTnT within the control group ( r  = 0.38 and 0.30, P <  0.01). There was no difference in post‐race cTnT (adjusted for pre‐race cTnT) between the three groups. None of the runners reported symptoms suggestive of acute myocardial infarction on follow‐up. These results demonstrate that marathon running is associated with an asymptomatic cTnT rise for all runners, and this rise is significantly correlated to baseline cTnT levels, in addition, marathon runners with pre‐existing cardiac pathology or who collapse at the finish line do not exhibit an increased cTnT rise compared to healthy runners.